From CAD to Robot: Undergraduate Capstone Design in Engineering Technology - Kuldeep S. Rawat; G.H. Massiha (Institute of Advanced Engineering and Science, 2013)
A novel senior project in designing and implementing a wheeled platform-based experimental mobile robot is discussed. This mobile robot design project was used as a platform to learn sensor interfacing, microcontroller programming, motor control, and electronic circuit design and troubleshooting. A specially designed proto board was used so that students could experiment with various types of sensors and supporting electronic circuitry. The modules implemented in this project are, servo motor control, infrared (IR)-based obstacle detection and avoidance, temperature sensing, and IR wireless communication. An 8-bit Peripheral Interface Controller (PIC) microcontroller, operating at 20MHz, was used as a programmable controller to monitor external environment through sensors and make appropriate decisions. PIC microcontroller was programmed using PICBasic PRO, a BASIC like high-level language. The implementation was divided into separate experiments, through which the students progressively completed the mobile robot. This progressive experimentation helped students develop their knowledge of interfacing, microcontroller programming, electronic control, circuit design, and troubleshooting in an incremental manner. The robot design experiments, sensor interfacing, electronic control, supporting circuitry, problems faced and troubleshooting during implementation are discussed in the paper.